“John A. MacMillan: Pioneer Missionary of Spiritual Warfare and the Believer’s Authority” - Paul King (Sekolah Tinggi Theologia Jaffray, 2016)
Many people associate teaching on spiritual warfare and the authority of the believer from charismatic or Word of Faith sources, especially like Kenneth Hagin. However, the original source of teaching on this doctrine comes from classic holiness roots in the Higher Life and Keswick movements, especially from John A. MacMillan, a missionary, writer, editor, and professor with the Christian and Missionary Alliance. In 1932 he wrote a series of articles entitled “The Authority of the Believer,” eventually published in book form, distributed widely and republished in other periodicals. MacMillan had a remarkable and extensive ministry in the exercise of the authority of the believer and spiritual warfare spanning more than thirty years. His experiences include divine protection, healing, divine intervention, power encounters with demonic forces, and teaching on territorial spirits and generational bondages. Numerous evangelical and charismatic leaders have quoted or referred to his teachings and principles.Banyak orang mengasosiasikan pengajaran peperangan rohani dan otoritas orang percaya dari karismatik atau sumber Firman Iman, terutama seperti Kenneth Hagin. Namun, sumber asli dari pengajaran doktrin ini berasal dari akar kekudusan klasik dalam gerakan Higher Life dan Keswick, terutama dari John A. MacMillan, seorang misionaris, penulis, editor, dan profesor dengan Christian and Missionary Alliance. Pada tahun 1932 ia menulis serangkaian artikel yang berjudul “Otoritas orang percaya,” akhirnya diterbitkan dalam bentuk buku, didistribusikan secara luas dan diterbitkan di majalah lainnya. MacMillan memiliki pelayanan yang luar biasa dan luas dalam pelaksanaan otoritas orang percaya dan peperangan rohani yang lebih dari tiga puluh tahun. Pengalamannya termasuk perlindungan ilahi, penyembuhan, campur tangan ilahi, pertemuan kuasa dengan kekuatan jahat, dan pengajaran tentang roh teritorial dan perbudakan generasi. Banyak pemimpin injili dan karismatik telah mengutip atau memakai ajaran dan prinsip-prinsipnya. Kata-kata kunci: otoritas percaya, peperangan rohani, hidup tahta, roh teritorial, C &MA, Higher Life, Keswick, karismatik, mengikat dan melepaskan